The nature of the companion star in Circinus X-1 - Johnston, H.; Soria, Roberto; Gibson, J. (Oxford University Press, 2016)
© 2015 The Authors. We present optical spectra and images of the X-ray binary Circinus X-1. The optical light curve of Cir X-1 is strongly variable, changing in brightness by 1.2 mag in the space of four days. The shape of the light curve is consistent with that seen in the 1980s, when the X-ray and radio counterparts of the source were at least ten times as bright as they are currently. We detect strong, variable H a emission lines, consisting of multiple components which vary with orbital phase. We estimate the extinction to the source from the strength of the diffuse interstellar bands and the Balmer decrement; the two methods give AV = 7.6 ± 0.6mag and AV > 9.1 mag, respectively. The optical light curve can be modelled as arising from irradiation of the companion star by the central X-ray source, where a low-temperature star fills its Roche lobe in an orbit of moderate eccentricity (e ~ 0.4). We suggest that the companion star is overluminous and underdense, due to the impact of the supernova which occurred less than 5000 yr ago.